Development of New Simulator Generating High Frequency Component of Ski Board Vibrations in Actual Skiing. (2015) - Shionoya, Akira; Shimizu, Yuta; Kenmotsu, Yusuke; Imamura, Akira; Uchiyama, Hisashi; Kimoto, Rika; Kawada, Yoshitaka
Abstract: The purposes of this study are to develop the new simulator generating high frequency component of a ski board vibration in skiing and to investigate the key factor to influence the ski sliding performance of the ski board. Using this simulator, a coefficient of kinetic friction ( μ k ) between the snow and the ski board with the vibration of 0 Hz (no vibration), 263 Hz and 361 Hz were investigated. Furthermore, a field experiment for verifying these experimental results using a simulator was carried out in a ski area. From these experiments, a high vibration frequency of the ranges from almost 200 Hz to 400 Hz occurred on a ski board has been thought to be key factor to influence the sliding performance of the ski board.